Echinococcosis in Pregnancy: A Systematic Review on Complications, Management, and Outcomes - Kiarash Kavari; Reza Ebrahimzadeh Mirzaei; Fatemeh Khajehasani; Nasrin Asadi; Mohammad Shafiee; Majid Fasihi Harandi (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Echinococcosis in pregnancy represents a complex clinical condition in terms of diagnosis and treatment with potential risk to both maternal and fetal health. There are limited clinical data on the nature and consequences of echinococcosis during pregnancy. This systematic review summarizes the current evidence on the clinical presentation, management, complications, and outcomes of echinococcosis during pregnancy. PubMed, Scopus, Web of Science, and Embase databases from 1990 to 2025 were queried. Sixty-seven articles met the inclusion criteria, and a total of 120 pregnant patients with echinococcosis were studied, of whom 118 were diagnosed with cystic echinococcosis (CE) and 2 were diagnoses with alveolar echinococcosis. Among patients with CE, the mean maternal age was 28 years old, and the liver was the most commonly affected organ (69%). Successful delivery of healthy infants was reported in 73% of the CE patients. Embryonic/fetal death was reported in 18% of cases, whereas preterm delivery was reported in 28% of pregnancies with available delivery data. The most common management strategy during pregnancy was the watch-and-wait approach (50%) followed by surgery (18%), percutaneous interventions (12%), albendazole therapy (9%), combined surgery and benzimidazole therapy (8%), and percutaneous interventions combined with albendazole (2%). Given the potential for serious maternal and fetal complications in pregnancy and the paucity of high-quality evidence in this area, there is a clear need for further well-designed clinical studies to improve our understanding of diagnostic approaches, clinical management, therapeutic strategies, and maternal and fetal long-term outcomes.